Recurrent esophagogastric variceal bleeding due to portal vein thrombosis caused by protein S deficiency - Zhou, Haoxiong; Xuan, Jieying; Lin, Xianyi; Guo, Yunwei (Endoscopy International Open, 2018)
Background and study aims Esophagogastric variceal bleeding (EGVB) is common in patients with portal vein thrombosis (PVT). Hereditary deficiencies in natural anticoagulant proteins, such as protein S, might contribute to PVT. However, recurrent EGVB caused by PVT in patients with protein S deficiency is seldom reported. Herein, we present the case of a 38-year-old man with protein S deficiency complicated with PVT. The patient suffered recurrent EGVB for 7 years. He underwent splenectomy plus pericardial revascularization and sequential endoscopic therapy, including one gastric variceal obturation (GVO) procedure and two esophageal variceal ligations (EVL) to eradicate the varices. Rivaroxaban was administrated to reduce risk of thrombotic events. The patient is currently well without rebleeding after 1 year of follow-up. To our knowledge there is no consensus on management of recurrent EGVB on the basis of thrombophilia complicated with PVT. According to our practice, sequential endoscopic therapy combined with anticoagulant appears to be effective and safe.